Oxford Centre for Animal Ethics Summer School Chronology - July 2018 - Oliver Wookey (Universitat Autonoma de Barcelona. Facultat de Dret, 2018)
Professor Marita Giménez-Candela and myself, on behalf of the ICALP and Master of Animal Law and Society, had the pleasure of attending the Fifth Annual Oxford Summer School on Animal Ethics. This chronology details certain elements of this Conference, highlighting the key aspects and, to demonstrate the types of ideas brought and shared, describes specifically the presentations of former members of the Master in Animal Law and Society at the UAB. This piece also presents my views on the successes of the Conference on both a personal and professional level.